MASYARAKAT DALAM PERKEMBANGAN TEKNOLOGI INFORMASI DAN REALITAS PERUBAHAN SOSIAL DI ERA POSTMODERN - Maharani, Ida Ayu Kartika (Institut Hindu Dharma Denpasar, 2019)
At present social changes that occur in the information revolution era, not only touch the appearance of government officials, politicians, and economic actors, but have penetrated the lifestyle and social behavior in the wider community, including the lifestyle and social behavior of young people. The existence of young people in the process of change and reform movement, is stated as one of the strengths of civil society that seems to be more easily adapted to the development of digital-based information and communication technology that is developing in digital native circles.The development of a society that is dominated by information technology, in addition to changes in social interaction patterns and ways of communicating, there have also been changes in people's attitudes and behavior in responding to the social realities that occur around them. This reality is not merely an observable object, but has gone beyond reality itself which is called hyperreality. Hyperreality intended here is an artificial or superficial reality, created through the aid of simulation technology and imaging engineering, which takes over the natural world of reality. These are said to be models of reality, which have no reference to reality or do not have a reference or reference to reality, but only refer to themselves.